A randomized Phase III trial of adjuvant S-1 therapy vs. observation alone in resected biliary tract cancer: Japan Clinical Oncology Group Study (JCOG1202, ASCOT). (15th February 2018) - Nakachi, Kohei; Konishi, Masaru; Ikeda, Masafumi; Mizusawa, Junki; Eba, Junko; Okusaka, Takuji; Ishii, Hiroshi; Fukuda, Haruhiko; Furuse, Junji
Abstract : A randomized Phase III trial for resected biliary tract cancer patients was started in September 2013 to confirm the superiority of adjuvant S-1 therapy to observation alone. Abstract: No standard adjuvant treatment has been established for patients with curatively resected biliary tract cancer. S-1 has been reported to show promising efficacy with mild toxicity profiles in patients with advanced biliary tract cancer, and adjuvant S-1 therapy has been demonstrated to provide survival benefit in patients with resected gastric cancer and pancreatic cancer. The aim of this open-label, multicenter, randomized Phase III trial is to confirm that adjuvant chemotherapy with S-1 would prolong overall survival in patients with resected biliary tract cancer. This study was activated in September 2013. A total of 350 patients planned to be enrolled from 36 Japanese institutions over a period of 4 years. At July 2017, the protocol was revised to increase power from 70% to 80%. Therefore, the planned total sample size is 440. The primary endpoint is overall survival. This trial is registered with the UMIN Clinical Trials Registry as UMIN000011688.